2020
DOI: 10.5999/aps.2019.00941
|View full text |Cite
|
Sign up to set email alerts
|

Urethroplasty of extensive penile urethral strictures with a longitudinal ventral tubed flap of penile skin (modified Orandi urethroplasty): 20 years of follow-up of two cases

Abstract: The surgical treatment of extensive urethral strictures remains a controversial topic; although techniques have evolved, there is still no definite method of choice. Since 1968, when Orandi presented an original technique for one-stage urethroplasty using a penile skin flap, the Orandi technique has become the most prevalently used one-stage procedure for anterior urethral strictures. We present a 20-year follow-up experience with one-stage reconstruction of long urethral strictures using a longitudinal ventra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…As opposed to the modification by Barbagli, the authors tubularize a longitudinal ventral flap after exciding the obliterative part of the urethra to overcome poor vascularity. Although limited by the small sample of only two patients, long-term follow-up of > 20 years revealed stable voiding characteristics [23].…”
Section: Penile Stricturesmentioning
confidence: 89%
See 1 more Smart Citation
“…As opposed to the modification by Barbagli, the authors tubularize a longitudinal ventral flap after exciding the obliterative part of the urethra to overcome poor vascularity. Although limited by the small sample of only two patients, long-term follow-up of > 20 years revealed stable voiding characteristics [23].…”
Section: Penile Stricturesmentioning
confidence: 89%
“…Another modification of Orandi's technique was recently presented in a case series by Heo et al [23]. As opposed to the modification by Barbagli, the authors tubularize a longitudinal ventral flap after exciding the obliterative part of the urethra to overcome poor vascularity.…”
Section: Penile Stricturesmentioning
confidence: 99%
“…When it comes to repairing complex anterior urethral strictures in a single procedure, Heo et al (16) demonstrated the long-term success of using a circular fascio-cutaneous flap from the distal penile. Median follow-up was 7.3 years (range 1 month to 19.5 years), median stricture length was 8.2 cm (range 0-24), and overall success rates at 1, 3, 5, and 10 years were 95%, 89%, 84%, and 79%, respectively.…”
Section: Penile Skin Flaps: Urethroplasty Utilizing a Skin Graft From...mentioning
confidence: 99%
“…Among the most commonly reported side effects were hemorrhage, urinary extravasation, necrosis of the penile skin, and a loss of penile feeling. Repair of long, difficult penile or penobulbar urethral strictures continues to be one of McAninch's most often performed surgeries (16) .…”
Section: Penile Skin Flaps: Urethroplasty Utilizing a Skin Graft From...mentioning
confidence: 99%
“…In addition to the anatomic description, the flap is also often described in the literature based on the eponym of the describing surgeon. For example, the longitudinal ventral penile skin flap with lateral pedicle placed as a ventral onlay is also referred to as the "Technique of Orandi" or "Orandi Flap" [27,28] . Further confusion can arise with modifications of classic descriptions, such as a tubularized "modified Orandi Flap" [29] .…”
Section: Types Of Penile Skin Flapsmentioning
confidence: 99%